2016
DOI: 10.1002/cjce.22461
|View full text |Cite
|
Sign up to set email alerts
|

Economic comparison of a continuous ABE fermentation with and without the integration of an in situ vacuum separation unit

Abstract: The development of renewable fuels has achieved enormous progress motivated by the rapid decline in petroleum resources and their oscillating price. After a wave of interest in bioethanol and biodiesel, biobutanol has been intensely investigated over the last decade and is considered a suitable renewable fuel. Biobutanol is most often produced through the Acetone-Butanol-Ethanol (ABE) bacterial fermentation process. This process is plagued, however, with high recovery costs because of the low final butanol con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 16 publications
1
9
0
2
Order By: Relevance
“…The main modeling and economic assumptions made in the analysis are presented in Table 5. Those values were selected based on previous relevant publications [8,31,[36][37][38] as well as on the authors' engineering judgement. In the case of SCA, the initial concentration of sugars in the fermentor is limited to 60 g/L and the conversion of sugars was assumed to be 85% (assuming equal conversion of pentoses and hexoses) with the remaining percentage converted to biomass cells.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main modeling and economic assumptions made in the analysis are presented in Table 5. Those values were selected based on previous relevant publications [8,31,[36][37][38] as well as on the authors' engineering judgement. In the case of SCA, the initial concentration of sugars in the fermentor is limited to 60 g/L and the conversion of sugars was assumed to be 85% (assuming equal conversion of pentoses and hexoses) with the remaining percentage converted to biomass cells.…”
Section: Methodsmentioning
confidence: 99%
“…This kind of uncertainty is usually not considered at all or is, at best, partially addressed by single-point sensitivity analysis where specific key parameters are varied independently. [38] This work presents a techno-economic analysis of two alternative process scenarios for a small-scale biorefinery that produces isobutanol from corn stover. The uncertainty in the estimation of the unit production cost associated with the choice of certain key parameters (e.g., sugars conversion, corn stover cost, enzyme price and loading ratio) is addressed by a Monte Carlo simulation.…”
Section: Introductionmentioning
confidence: 99%
“…The potential of large-scale cellulosic butanol production is limited by the low efficiency of the pretreatment process as well as the extensive downstream processing requirement. Studies have revealed both operations as potentially driving the production cost of cellulosic butanol [1][2][3][4]. Pretreatment is essential to reduce the recalcitrant structure of lignocellulosic materials and therefore results in better sugar yield after the enzyme hydrolysis process [5].…”
Section: Introductionmentioning
confidence: 99%
“…Several available works compared the energy performance of the product separation process [1,4,8,10,13]. However, researchers have agreed that direct comparison among the available literature is hard due to the various operating conditions and system assumptions used [18].…”
Section: Introductionmentioning
confidence: 99%
“…At the best of our knowledge, a scheme of production of ABE, butyric acid (BA), furans and phenolic compounds by liquid-liquid extraction has been not studied in the literature. Process modeling is an important tool to determinate the viability of new processes [25][26][27][28]. For these reasons, in this work, a detoxification system with simultaneous saccharification, fermentation, and extraction (SSF-E) ( Fig.…”
Section: Introductionmentioning
confidence: 99%